Coautoria, conflito da vontade e testemunho: outras intervenções e compreensões psicológicas em diálogo com o pensamento de Hannah Arendt. - Silva, Itala Daniela da (2022)
This work discuss about the Arendt’s concepts of co-authorship, conflict of will and testimony, with the goal to present with the aim of presenting other interventions and understandings of psychological practice in dialogue with Hannah Arendt's view. This qualitative research began with a systematic review. From the bibliographic survey it was possible to understand which Arendt’s concepts are present in the field of Psychology in Brazil. After the systematic review, a meta-analysis was carried out on the dissertations of the Amor Mundi group, which works on psychological practices in dialogue with Arendt's thinking. In addition to these methodological resources, the researcher's journal was used as a source of narrative to weave the analyses. By articulating the experiences contained in the research and in the journal, it was possible to discuss Arendt's concepts that enable new understandings and interventions in psychological practice. The concept of co-authorship, conflict of will and testimony intertwine and points to the webs of human relationships, the tension between will and power, the narrativity and the speech as significant themes for the construction of new ways of intervening in a psychological relationship. Such concepts summon the psychology professional to reposition the relationship, inviting him to assume the condition of co-author and witness, fundamental for people to build new existential destinations. Finally, such discussions still stress the Psychology's commitment to the active life that occurs in the midst of human relationships and has a resistance that no theory can presuppose.